2009
DOI: 10.1038/onc.2009.377
|View full text |Cite
|
Sign up to set email alerts
|

c-Myc overexpression promotes a germinal center-like program in Burkitt's lymphoma

Abstract: The germinal center (GC) reaction has a pivotal function in human B-cell lymphomagenesis. Genetic aberrations occurring during somatic hypermutation and class switch recombination deregulate key factors controlling B-cell physiology and proliferation. Several human lymphoma entities are characterized by a constitutive GC phenotype and ongoing somatic hypermutation, but the molecular basis for this phenomenon is only partly understood. We have investigated the reasons for a constitutive GC-like program in Burki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 52 publications
2
15
0
Order By: Relevance
“…Burkitt lymphoma is the prototypic GC-like lymphoma 27 and, in agreement with our results on CD300a expression by GC cells, we found that, except for the BJAB cell line that expresses low amounts of CD300a, the rest of the Burkitt lymphoma cell lines (n ϭ 7) are negative for CD300a expression. On the other hand, the non-Hodgkin lymphoma cell lines REC-1 (mantle cell lymphoma) and SUDHL5 (diffuse large B-cell lymphoma with ABC-like phenotype) are positive for CD300a expression, which is in agreement with the origin of these lymphomas, namely, pre-GC B cells and activated B cells, respectively.…”
Section: Cd300a Is Differentially Expressed On Human B-cell Subsetssupporting
confidence: 79%
“…Burkitt lymphoma is the prototypic GC-like lymphoma 27 and, in agreement with our results on CD300a expression by GC cells, we found that, except for the BJAB cell line that expresses low amounts of CD300a, the rest of the Burkitt lymphoma cell lines (n ϭ 7) are negative for CD300a expression. On the other hand, the non-Hodgkin lymphoma cell lines REC-1 (mantle cell lymphoma) and SUDHL5 (diffuse large B-cell lymphoma with ABC-like phenotype) are positive for CD300a expression, which is in agreement with the origin of these lymphomas, namely, pre-GC B cells and activated B cells, respectively.…”
Section: Cd300a Is Differentially Expressed On Human B-cell Subsetssupporting
confidence: 79%
“…It has recently been shown that c-Myc overexpression is responsible for the "centroblast-like" phenotype of the Burkitt lymphoma cells and that treatment of these cells with a specific c-Myc inhibitor, 10058-F4 inhibits expression of proteins associated with the germinal center phenotype, such as Bcl-6. 31 We therefore explored whether the modification of this "germinal center phenotype" was also associated with a change in the regulation of Puma expression. Indeed, we observed a parallel decrease in the levels of Bcl-6 and Puma proteins from BL41 cells in response to treatment with various doses of 10058-F4, whereas the levels of Bcl-2 or GAPDH were not altered ( Figure 2D).…”
Section: Expression Of Puma Was Associated With Germinal Center-like mentioning
confidence: 99%
“…Our work has also led to the discovery of a SHP2-dependent GC lymphoma proliferative signature comprising a set of genes that are overexpressed in GC lymphomas. 5,6 Depletion of SHP2 led to a similar impairment of GC lymphoma proliferative phenotype signature expression, demonstrating that SHP2 is a high-quality target in GC lymphomas.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, our data indicate that SHP2 activation of ERK1/2 might be responsible for the transcriptional activation of c-Myc, which mediates an increase in the expression of "GC lymphoma phenotype proteins". 5,6 SHP2/ERK signaling mediated c-Myc Ser62 phosphorylation thus stabilizing c-Myc protein and enhancing its transcriptional activity. 19,30 Conversely, ERK activation phosphorylates GSK3b Ser389 in the C-terminus, which causes GSK3b inactivation and inhibits c-Myc Thr58 phosphorylation from mediating c-Myc proteolysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation